(untitled) (Journal of Hama University, 2024)
Aim of study: To compare the shear strength between bulk composite and fiber reinforced bulk composite. Materials and methods: This study included 40 newly extracted upper premolars for orthodontic reasons, were randomly divided into two groups according to the restored material in the following order: Group1 (n=20): Bulk composite (Tetric® N-Ceram Bulk Fill, Ivoclar Vivadent, USA), and Group2 (n=20): Fiber reinforced bulk composite (Polydentia, Switzerland). The cusps were removed from the entire premolars of the sample at a level of the cementoenamel junction using diamond disc (Horico, Germany) so that the dentin surface became exposed. The premolars were fixed on acrylic molds with fixed dimensions 2.5 cm × 2.5 cm × 2.5 cm so that the root is embedded in the acrylic mold. A metal mold was made for the research, containing in its center a cylindrical cavity with dimensions: 3 mm in diameter and 4 mm in height, then it was placed on the surfaces of all the samples to compact the resin within the central cavity according to the distribution of the groups. The samples were prepared for testing, then they were transferred to the universal testing machine (Testometric AX 114, Universal Testing Machine), and each of them was subjected to a shear strength test after the moving head of the device was set a speed of 1 mm min until failure occurred. Results: The values of shear strength in the fiber reinforced bulk composite group were higher than in the bulk composite group.